Strategies employing transition-metal free conditions for C-C bond formation in indoles - Ghodake, Balaji M.; Paul, Sayantan; Bhattacharya, Asish K. (ChemistrySelect, 2024)
Indole motifs are omnipresent in nature and can be found in many natural products as well as pharmaceuticals. It is for this reason synthetic transformations of indole have become a topic of interest for the organic and medicinal chemist community for decades. In this review, we have emphasized the functionalization of indoles via transition-metal-free approaches. This review touches on many aspects in different sub-sections, which gives a proposition of the tactics employed for the functionalization of indoles and an overview of the road ahead. In this review, essentially transition-metal-free conditions for C-C bond formation reactions in indoles has been explored. This review describes various approaches of functionalization at the C-2, C-3, C-4 and C-7 position of indoles which comprises arylation, alkenylation, acylation, formylation, alkylation, bisindolyl and cyclization strategies. Also, strategies incorporating N-alkylation/arylation has also been covered. image
Keywords: Alkylation; Arylation; formylation; Indole; transition-metal free

Catalyst and transition-metal free 1,6-conjugate addition of azobisisobutyronitrile: access to isobutyronitrile containing diarylmethanes - Mamale, Ajay G.; Ghodake, Balaji M.; Gonnade, Rajesh G.; Bhattacharya, Asish K. (Organic & Biomolecular Chemistry, 2025)
A catalyst and transition-metal free 1,6-conjugate addition of azobisisobutyronitrile to para-quinone methides for the synthesis of isobutyronitrile containing diarylmethanes has been achieved. This protocol enables the synthesis of isobutyronitrile containing diarylmethanes in good yields and with a broad substrate scope. This is the first example wherein azobisisobutyronitrile has been used as a cyanide source for 1,6-conjugate addition under catalyst and metal-free conditions.

One-pot synthesis of N-arylated benzotriazoles and benzotriazinones via in situ diazotization and aryne trapping - Ghodake, Balaji M.; Bhattacharya, Asish K. (Organic & Biomolecular Chemistry, 2026)
N-Arylated benzotriazoles and 1,2,3-benzotriazin-4-ones are important structural motifs in synthetic and medicinal chemistry, valued for their distinctive frameworks and functional versatility. We have developed an efficient, one-pot strategy for the synthesis of N-arylated benzotriazoles and benzotriazinones. The protocol involves in situ diazotization of o-phenylenediamine or 2-aminobenzamide using tert-butyl nitrite (tBuONO), followed by trapping of arynes generated in situ from 2-(trimethylsilyl)aryltriflates in the presence of CsF. The methodology exhibits broad functional-group tolerance and was successfully applied to 47 substrates, affording yields in the range of 60-85%. Furthermore, gram-scale synthesis highlights the operational simplicity and practical utility of this approach.